Acceptance and Commitment Therapy for the Treatment of Posttraumatic Stress Among Adolescents. (July 2014) - Woidneck, Michelle R.; Morrison, Kate L.; Twohig, Michael P.
The number of individuals who meet diagnostic criteria for posttraumatic stress disorder (PTSD) is a small percentage of those exposed to trauma; many youth who do not meet criteria for PTSD continue to experience problematic posttraumatic stress (PTS) symptomology. Acceptance and commitment therapy (ACT) has shown preliminary effectiveness in the treatment of adult PTSD, but its effectiveness in treating PTS in youth is unknown. Using a multiple-baseline design, this study investigated the effectiveness of 10 weeks of ACT to treat PTS in youth. Four adolescents from a community sample and three adolescents from a residential sample participated. The Clinician Administered PTSD Scale for Children and Adolescents (CAPS-CA), Child PTSD Symptom Scale (CPSS), and Comprehensive Quality of Life Scale were completed at pretreatment, posttreatment, and 3-month follow-up. Individuals reported baseline data for 7 to 66 days. Symptom and process measures were completed at each session. Results revealed a decrease in PTS symptomology across both samples with mean reductions in self-reported PTS symptomology at posttreatment of 69% and 81% for the community and residential samples, respectively, and an overall 68% and 84% respective reduction at follow-up. Reductions in clinician rated measures of PTSD were observed for all participants with mean reductions of 57% and 61% in the community and residential samples at posttreatment, and 71% and 60% at follow-up, respectively. Results provide preliminary support for ACT as a treatment for adolescent PTS. Empirical and clinical implications as well as limitations and future directions are discussed.